(untitled) (Emergency Care Journal, 2024)
We report the case of a young male patient who presented to our emergency department complaining of a transient headache and a feeling of motor impairment in his right lower limb, both of which completely resolved spontaneously. After a few minutes of his arrival, he developed a locked-in sensation with anxiety and agitation, followed by a rapid onset of left facio-brachio-crural hemisyndrome. Contrast-enhanced CT of the brain and neck showed the occlusion of the proximal-intermediate basilar artery. Acute basilar artery occlusion (BAO) is a rare life-threatening stroke that requires prompt diagnosis and appropriate treatment to avoid rapid fatal complications (coma and death). The prognosis is poor, with long-lasting sequelae in the survivors. The diagnosis is often difficult since BAO accounts for only 1% of all strokes, and the prodromal symptoms are often very mild, transient, and non-specific, such as nausea, dizziness, headache, confusion, and vertigo. In the presence of convulsion-like symptoms or an unexplained altered level of consciousness, emergency physicians should always consider BAO in the differential diagnosis.